Social Entrepreneurship In The New Economy Among The Younger Generation - Zainul Wasik; Suwandi S. Sangadji; Dedy Iswanto (PT. Mawadaku Sukses Solusindo, 2023)
Purpose: This essay aims to reconstruct young people's understanding of and attitude towards social entrepreneurship as a field of endeavour critical to developing crucial competencies in the New Economy. The study also aims to describe young people's perceptions of their willingness to participate in society and the current economy as agents. Design/methodology/approach: In order to accomplish this, a diagnostic study (based on a so-called task catalogue) was carried out with a group of more than 500 students in Indonesian vocational high schools, senior high schools, and private schools, as well as three workshops with students from particular school types. Findings: According to the study, students are aware of the possibilities of engaging in social activism through broadly construed social entrepreneurship and third sector involvement. It was also proven that they are well cognizant of the opportunities and requirement for action in this regard. The materials that students have discussed transfer into skills required in the New Economy. Research limitations/implications: A lot of variables that could influence teenage behaviour must be taken into account in modern study. These difficulties will undoubtedly merit consideration throughout the formulation and creation of the research's tools in further in-depth studies. Practical implications: Young people's social entrepreneurship is constantly evolving, and even though its focus shifts (from shared management activities to civic engagement and social solidarity activities), it always refers to collaborative efforts on the cusp of economic and social reality. Young people's attitude towards carrying out duties that are beneficial to society is also evolving. Young people view them as a chance to address both societal issues and the difficulties posed by the postmodern world's transformations. Social implications: Young people are more conscious and involved citizens as well as more responsible future members of the New Economy thanks to the competencies they have acquired. Originality/value: The paper reconstructs the tools, strategies, and perspectives of young people towards the agency opportunities provided by social entrepreneurship. The knowledge that was gathered was examined in light of the project's competency-based competence issues.